The claustrum and insula in Microcebus murinus: a high-resolution diffusion imaging study - Soyoung ePark; Mike eTyszka; John M Allman; John M Allman (Frontiers Media S.A., 2012)
The present study explores the connectivity of the claustrum and insula in the mouse lemur (Microcebus murinus) using high angular resolution diffusion imaging (HARDI with 72 directions), with a very small voxel size (90 micra), and probabilistic fiber tractography. Our data indicate that the claustrum connects with many cortical areas and the olfactory bulb; its strongest probabilistic connections are with the entorhinal cortex, suggesting that the claustrum may have a role in spatial memory and navigation. By contrast, the insula connects with many subcortical areas, including the brainstem and thalamic structures particularly involved in taste and visceral feelings. The insula in the Microcebus connects with the dorsolateral frontal cortex in contrast to the mouse insula, which has stronger connections with the ventromedial frontal lobe. This connectivity in the Microcebus is consistent with the dorsolateral expansion of the frontal cortex in primates. In spite of these connectional differences between the claustrum and insula, their close juxtaposition and common gene expression point to the cortical affinities of the claustrum. Overall, the connections of the Microcebus claustrum and insula are similar to those of the rodents, cat, macaque, and human, validating these results. High angular and spatial resolution diffusion tensor imaging offers the advantages that it is non-destructive, requires no surgical interventions, and the connection of each and every voxel can be mapped, whereas in conventional tractography only a few specific tracer injection sites can be assayed. Also, the brain can be sectioned computationally into any desired plane for analysis.